Digital Transformation and ICT Development in Uzbekistan's Digital Economy - Saatova Lolakhon Ergashevna (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines the development trajectory of information and communication technologies (ICT) and their role in establishing the digital economy in the Republic of Uzbekistan during the transformative period of 2015-2024, a critical phase marked by systematic digital transformation initiatives under national strategic frameworks. The research aims to assess the effectiveness of ICT infrastructure development and digital service integration across economic sectors in Uzbekistan's transition toward a digitally-driven economy. Employing comparative economic analysis, systems approach, and observation methods, the study analyzes comprehensive statistical data from the International Telecommunication Union, Open Data Portal of Uzbekistan, and governmental reports, examining key indicators including internet penetration rates, broadband subscriptions, fiber-optic network expansion, mobile internet coverage, and e-government service adoption across banking, industry, agriculture, and education sectors. Empirical findings reveal substantial growth in internet users from 43.6% to 85%, broadband subscribers increasing from 5.2 million to 23 million, fiber-optic networks expanding from 16,000 km to 100,000 km, and electronic public services rising from limited availability to 595 services by 2024, with sector-specific ICT penetration reaching 85% in banking and finance. The novelty lies in providing systematic longitudinal evidence of digital transformation outcomes under the